The Spirit of Human Fraternity Pervades Sabah’s Inter-Religious Landscape Preserving Unity in Diversity - Sintang, Suraya; Mohd. Khambali @ Hambali, Khadijah; Mohd. Khalli, Mohd. Nazmi; Ationg, Romzi; Marinsah, Syamsul Azizul; Mohd. Yakin, Halina Sendera (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
Document on Human Fraternity for World Peace and Living Together is a document of joint common ground between Muslims and Christians. It reinforces the initiative to work together for world peace. It has inspired the spirit of fraternity based on the teaching inherent in Muslim and Christian Revelations. This paper presents a portion of a study’s result on how the fraternity spirit penetrates the religious communities in Sabah to live together in accommodative relationships and open-minded attitudes. The paper employed a qualitative approach to designing a case study in Keningau district in the interior division of Sabah. The data collection involves ethnographic fieldwork by conducting interviews with religious leaders and selected local people with mixed-faith families and participant observation in several villages related to this study. The findings indicate that the Muslims and Christians in Sabah can be characterized as brothers and sisters and inspired to be an example of fraternal friendship. These attitudes have been attributed to them: displaying respect for different religions, being committed to fostering peace, being open to differences, and being willing to coexist in proximity. Hence, the spirit of human fraternity pervades Sabah’s inter-religious landscape, which has preserved unity in diversity.